ISU-ISU TERKINI TENTANG PENGGUNA Dl MALAYSIA - Zakaria, Zalina (Jurnal Syariah, 2019)
Escalating inflation, rapid industrialization, high pressure selling techniques and sophisticated goods and services have forced many consumers to re-evaluate their position vis-a-vis their economic stand, bargaining power and redress for their grievances and their health. Due to these, issues have struck many consumers from day to day. The issues are relevant to many since all are consumers. Yet, not so many realize their rights and which the laws will protect them, especially when the laws are scattered and in some instances, none is available. The article s modest aim is to sketch the latest issues plaguing consumers in Malaysia and help consumers attain their understanding of matters pertaining to consumerism.